The Additional Value of a Pneumatic Leg Brace in the Treatment of Recruits with Medial Tibial Stress Syndrome; a Randomized Study. Issue 4 (1st December 2010) - Moen, Maarten Hendrik; Bongers, T; Bakker, EWP; Weir, A; Zimmermann, WO; van der Werve, M; Backx, FJG
Abstract : Objective: To study the additional effect of a pneumatic leg brace with standard rehabilitation for the treatment of medial tibial stress syndrome (MTSS) in recruits. Methods: In a single blinded randomized study, 15 recruits (age 17-22) followed a rehabilitation programme consisting of leg exercises and a graded running programme. Recruits performed daily exercises and ran three times a week. The running programme consisted of 6 consecutive phases. One group was, after randomization, additionally provided with a pneumatic leg brace. Follow-up was provided every other week. Days to completing the running programme was the primary outcome measure, the Sports Activity Rating Scale (SARS) score and satisfaction with the treatment were secondary outcome measures. Results: In total 14 recruits completed the rehabilitation programme. No differences were found in the number of days until phase six of the running schedule was finished between the brace and the control group (Brace 58.8 ± 27.7 (mean ± SD) vs Non-Brace 57.9 ± 26.2 (mean ± SD, p = 0.57). Also no differences were found in the SARS scores between the groups. Overall satisfaction with the treatment was 6.4 ± 1.1 (mean ± SD) on a 1-10 scale for the brace group and 7.1 ± 0.7 (mean ± SD) for the control group (p = 0.06). Comfort of the brace was assessed as 4.8 ± 1.3 (mean ± SD) on a 1-10 scale. Conclusions: No additional large effect of the pneumatic leg brace could be found in recruits and wearing of the brace was not feasible, since the wearing comfort was low.